Mitral Valve Surgery in Ibn Albitar Center for Cardiac Surgery from 2004 To 2018 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Discuss the outcome of the mitral valve surgery in Ibn Al Bitar Center for cardiac surgery from  2004 to 2018  with 2250 patients, Assesses the factors of risk for surgical mortality in those who perform surgery for mitral valve and Improve that the outcome of mitral valve replacement much better than other types of mitral valve surgery. The type of this research is a retrospective of a total of 2250 patients who performed mitral valve surgery from  2004 to 2018 in Ibn Al Bitar Center for cardiac surgery (Baghdad /Iraq). The mitral valve surgery was mitral valve replacement 82.5 %, closed mitral commissurotomy 7.1%, open mitral commissurotomy  4.9% and redo mitral valve surgery  5.5 %. There are only 22 patients die and the causes of the death were Hemorrhage and cardiac tamponade in 9 patients (40%),  infective endocarditis in 6 patients (27.2%), heart failure in 4 patients (18.1%), and thromboembolism in 3 patients (13.6%).  This study showed that Mitral valve surgery will be performed with a suitable operative mortality that compares favourably with leads to different printed series and future survival for bicuspid valve replacement square measure wonderful addition to it the incidence to reoperation was considerably less than closed and open commissurotomy, so the bicuspid valve replacement is that the best style of bicuspid valve surgery.